Integrality and comprehensiveness of service provision in Primary Health Care in Brazil (2012-2018) - Allan Nuno Alves de Sousa; Helena Eri Shimizu (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze comprehensiveness elements in Primary Care in Brazil, between 2012 and 2018, considering preventive and assistance aspects, pointing out advances and obstacles to its improvement in different contexts. Methods: a retrospective longitudinal study using data from the Brazilian National Program for Improving Access and Quality in Primary Care. 15,378 teams were selected that participated in both 1st and 3rd cycles of the program. Results: improvements were found in the prevalence of teams that ensure preventive and assistance care for priority groups, who develop promotion actions, offer essential procedures, including oral health, carry out home visits, receive support from Extended Family Health and Primary Care Center, offer integrative and complementary practices and develop intersectoral actions. Conclusions: there has been an improvement in comprehensiveness in Primary Health services, but problems remain that still need to be faced for their improvement.